Renewal of wheat cultivars enhances ozone resistance in yield but detrimentally impacts quality: a survey of Chinese wheat - Yinsen Qian; Zheng Zhao; Yifan Cao; Quan Ma; Nanyan Zhu; Lingqi Song; Min Zhu; Min Zhu; Chunyan Li; Chunyan Li; Jinfeng Ding; Jinfeng Ding; et al. (Frontiers in Plant Science)
The aggravation of ozone (O3) pollution poses a significant threat to agricultural production. With China being the leading wheat producer of the world, contributing 17.8% to global output, the vulnerability of wheat to O3 is of particular concern. Despite extensive research on the impacts of O3 on wheat production and the ongoing development of new wheat cultivars over the years, a connection between yield loss and the released ages of wheat cultivars under O3 stress remains unestablished. Addressing this, the experiment was carried out at the Yangzhou Rice and Wheat Free-air Gas Concentration Enrichment (FACE) Testing Base in China, using 17 wheat cultivars developed since the 1970s as experimental materials. The elevated O3 concentration in the test was 1.5 times higher than that in a normal atmosphere. The results indicated that O3 led to a significant reduction in wheat yield of 18.19%. The yield of cultivars released in the 1970s, 1980s, 1990s, and after 2000, decreased by 24.9%, 23.3%, 19.8%, and 14.7%, respectively. Overall, the direct effect of 1,000-grain weight on yield was the most significant, followed by the number of grains per spike, whereas the number of spikes contributed least to the yield components. To enhance resistance to O3 stress in future breeding efforts, increasing the 1,000-grain weight should be a primary objective. Our findings also revealed that elevated O3 concentration led to higher sedimentation values and protein content while lowering bulk density, hardness, and starch content. As the release age approaches, the rate of decrease in bulk density diminishes gradually. In terms of hardness, sedimentation value, and starch content, varieties released in the 1990s exhibited less sensitivity, whereas those released after the 2000s experienced the most significant changes in protein content. It is worth noting that the impact on the nutritional quality of modern cultivars is particularly significant, particularly regarding starch and protein content. Stress indices indicate that the cultivars released after 2000 exhibit stronger resistance to yield loss. The Yangmai series cultivars appear to be promising parental lines for future breeding programs aimed at developing O3-resistant wheat.